Perencanaan Inovasi Kewirausahaan Lembaga Dakwah - Aswari, Nuha Nabila; Castrawijaya, Cecep (Institut Agama Islam Negeri Kerinci, 2024)
Planning entrepreneurial innovation in da'wah institutions is a strategic effort to combine social and religious missions with entrepreneurial principles. The aim of this planning is to increase the economic independence of Da'wah institutions, expand their reach, and make a greater contribution to society. Entrepreneurial innovation involves developing business models that are in line with Islamic values, diversifying funding sources, and utilizing digital technology to optimize operations and da'wah activities. The planning process starts with analyzing the needs and potential of the institution, determining the entrepreneurial vision and mission that are in line with the goals of Da'wah, and then implementing innovative programs. The main challenge in implementation is maintaining a balance between commercial objectives and missionary objectives, as well as creating a model that is sustainable in the long term. We hope that da'wah institutions can achieve economic independence and strengthen their position as agents of social change with broad impacts through effective planning